A Promising Material by Using Residue Waste from Bisphenol A Manufacturing to Prepare Fluid-Loss-Control Additive in Oil Well Drilling Fluid - Zhang, Zhi-Lei; Zhou, Feng-Shan; Zhang, Yi-He; Huang, Hong-Wei; Shang, Ji-Wu; Yu, Li; Wang, Hong-Zhen; Tong, Wang-Shu (Journal of Spectroscopy, 2013)
The residues mixture from Bisphenol A manufacturing process was analyzed. Fourier transform infrared (FTIR) spectroscopy, gas chromatography-mass spectrometry (GC-MS), and nuclear magnetic resonance (NMR) were used to characterize the residues. The results indicated that the residues were complex mixture of several molecules. 3-(2-Hydroxyphenyl)-1,1,3-trimethyl-2,3-dihydro-1H-inden-5-ol and phenol were the main components of the residues. The technical feasibility of using it as phenol replacement in fluid-loss-control additive production was also investigated. The fluid-loss-control capacity of the novel additive was systematically investigated. It was discovered that the well fluid-loss performance of the prepared additive can be achieved, especially at high temperature.